Implikasi Perkembangan Peserta Didik dalam Pembelajaran di Kelas 6 SD - Atikah Zahrani Purba; Bintang Mahrani Abdullah; Friska Widia; Hilda Melani Purba; Novia Rahmadani Harahap; Ramadan Lubis (Lembag, 2025)
This research aims to examine the development of 6th grade elementary school children, with a focus on physical, cognitive, emotional, spiritual and social aspects. The research method used is qualitative with a descriptive approach, which focuses on understanding phenomena through observation, interviews and documentation. The research subject is a child named Ahmad Pandi Prasetya, who is now in grade 6 of elementary school. The results showed that Pandi's physical development was within the normal range with a height of 133 cm and a weight of 28 kg. The results showed that the subject's physical development was in accordance with the average age, with a height of 133 cm and a weight of 28 kg. In the cognitive aspect, Pandi showed good drawing skills and was quite good. In the emotional aspect, Pandi is able to recognize and manage his feelings, even though he still needs parental assistance. The spiritual aspect shows that Pandi is still not consistent in his worship, Pandi's worship is still often broken, but Pandi's parents still remind him to continue praying 5 times a day, Pandi's parents also advise Pandi slowly and try to understand Pandi, Pandi's parents believe that if children are told in a gentle way, children will understand and slowly change for the better. In the social aspect, Pandi turns out to be a child who lacks socialization, because Pandi is a child who spends his time at home and rarely leaves the house to socialize, he also has only a few friends. Overall, this research found that the subject's development was still not very good and perfect according to his age stage.